2017
DOI: 10.20546/ijcmas.2017.609.309
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Endoparasites in Captive Pheasants in Arignar Anna Zoological Park, Vandalur, Chennai, India

Abstract: ) and mixed infections (57.89%). Based on this study, the major causes for endoparasitism were identified and discussed. Important management measures were suggested to prevent endoparasites in order to promote the health of birds from parasitic infection. K e y w o r d sCaptive pheasants, Zoological park, Chennai.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Jaiswal et al (2013) reported endoparasitic infections in Indian peacocks of Veterinary College Campus, Mathura and found eggs and oocysts of cestodes and coccidia belonging to Eimeria and Isospora species. Pradeep et al (2017) reported incidence of endoparasites in captive pheasants in Arignar Anna Zoological Park, Chennai and revealed the presence of Ascaridia, Capillaria sp., Strongyloides sp., Strongyle, oocyst of Eimeria sp. An incidence of 88.33% helminthic parasitic infections was reported by Kashid et al (2003) in peacocks in Maharashtra.…”
Section: Resultsmentioning
confidence: 99%
“…Jaiswal et al (2013) reported endoparasitic infections in Indian peacocks of Veterinary College Campus, Mathura and found eggs and oocysts of cestodes and coccidia belonging to Eimeria and Isospora species. Pradeep et al (2017) reported incidence of endoparasites in captive pheasants in Arignar Anna Zoological Park, Chennai and revealed the presence of Ascaridia, Capillaria sp., Strongyloides sp., Strongyle, oocyst of Eimeria sp. An incidence of 88.33% helminthic parasitic infections was reported by Kashid et al (2003) in peacocks in Maharashtra.…”
Section: Resultsmentioning
confidence: 99%